1995
DOI: 10.1111/j.1432-1033.1995.tb20364.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Proteolytic Thrombin Fragments Formed after Cleavage with Rat Mast Cell Protease 1

Abstract: We have previously identified rat mast cell protease 1 (RMCP-I), a chymotrypsin-like secretory granule serine protease, as a potent inactivator of thrombin. The present study outlines the cleavage pattern obtained after degradation of thrombin by RMCP-1. The cleavage sites in thrombin were identified by N-terminal amino acid sequence analysis of recovered thrombin fragments. Incubation of thrombin with RMCP-1 resulted in the rapid formation of a 37-kDa fragment, due to cleavage of the PhelG-GlylF bond in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Earlier studies showed that rat chymase can convert intact 38 kDa thrombin to a 37 kDa fragment without loss of catalytic activity (31). Possibly, the small amounts of chymase still present in the NDST-2 -/cell cultures (6) are sufficient to cause this conversion but not further degradation during the time period studied.…”
Section: Resultsmentioning
confidence: 91%
“…Earlier studies showed that rat chymase can convert intact 38 kDa thrombin to a 37 kDa fragment without loss of catalytic activity (31). Possibly, the small amounts of chymase still present in the NDST-2 -/cell cultures (6) are sufficient to cause this conversion but not further degradation during the time period studied.…”
Section: Resultsmentioning
confidence: 91%
“…Both S-2586 and a macromolecular substrate, thrombin, were used as substrates. We have previously shown that thrombin is degraded by RMCP-1 in a process that is accompanied by inactivation of the coagulation enzyme [28]. Endogenous MC heparin PG gave a maximal approx.…”
Section: Activation Of Rmcp-1 By Heparinmentioning
confidence: 93%
“…Electrophoresis was performed at 12 mA for ∼18 h. After electrophoresis, the gel was stained with Coomassie brilliant blue and subsequently subjected to fluorography. NH 2 -terminal sequences were determined as previously described ( 29 ).…”
Section: Methodsmentioning
confidence: 99%